DESIGN AND IMPLEMENTATION OF ADVANCED PERIODIC CONTROLLERS FOR A FAULT-TOLERANT PMSM DRIVE SYSTEM - Hendriyono, Devi
The surface permanent magnet synchronous motor drive system has been widely used in the industry due to its high power density, high efficiency, and easy to control. In this thesis, advanced periodic controllers including a speed-loop frequency-adaptive periodic controller and a currentloop optimal harmonic controller are proposed to improve the performance of the fault-tolerant drive system. The frequency-adaptive periodic controller has simple computation, easy implementation, and on-line self-tuning and the optimal harmonic periodic controller has a fast dynamic response, and high accuracy to remove certain harmonics. The fault-tolerant method including a fault detection, a diagnosis, an isolation and a fault control scheme is proposed to improve the reliability of the SPMSM drive system. The faulty conditions that consist of an open-circuit and a short-circuit are investigated to show the improved performance. A digital signal processor, TMS320F2808, manufactured by Texas Instruments, is used to execute the proposed fault-detection, fault-diagnosis, fault-isolation, frequency-adaptive, and optimal harmonic periodic controller algorithms. Experimental results show the proposed frequencyadaptive periodic controller can provide better performance than the PI controller including transient responses, load disturbance responses, and tracking responses. It also shows that the proposed optimal harmonic periodic controller for the current-loop can effectively improve the total harmonic distortion of the drive system.